Holiday, Just One Day out of Life: Birth Timing and Postnatal Outcomes - Jacobson, Mireille; Kogelnik, Maria; Royer, Heather (Journal of Labor Economics, 2021)
Fewer births occur on major US holidays than would otherwise be expected. We use California data to study the nature and health implications of this birth date manipulation. We document 18% fewer births on the day of and just after a holiday. Cesarean sections account for roughly half of the decline. “Missing” holiday births are displaced to a window of time 11 days before the holiday through 16 days after the holiday. High-risk births are more likely to be rescheduled. Despite the change in timing, we find little evidence of any adverse health consequences for babies born around a holiday.